Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1074/jbc.c500353200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Transcriptional Activity of c-Fos by ERK

Abstract: The activation of the activating protein-1 (AP-1) family of transcription factors, including c-Fos and c-Jun family members, is one of the earliest nuclear events induced by growth factors that stimulate extracellular signal-regulated kinases (ERKs). In the case of c-Fos, the activation of ERK leads to an increased expression of c-fos mRNA. In turn, we have recently shown that ERK phosphorylates multiple residues within the carboxylterminal transactivation domain (TAD) of c-Fos, thus resulting in its increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(181 citation statements)
references
References 17 publications
10
163
0
1
Order By: Relevance
“…Isomerization of proline (Pro) residues by this protein has been shown to promote dephosphorylation of various molecules by PP2A (Zhou et al, 2000;Yeh et al, 2004;Monje et al, 2005). Pin1 binds Ser/Thr-Pro motifs through its WW motif and binds to a diverse set of substrates, including Cdc25 and Tau (Zhou et al, 2000;Stukenberg and Kirschner, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Isomerization of proline (Pro) residues by this protein has been shown to promote dephosphorylation of various molecules by PP2A (Zhou et al, 2000;Yeh et al, 2004;Monje et al, 2005). Pin1 binds Ser/Thr-Pro motifs through its WW motif and binds to a diverse set of substrates, including Cdc25 and Tau (Zhou et al, 2000;Stukenberg and Kirschner, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2C), indicating that Pin1 is still functioning in FGFR2-enhanced Runx2 protein stabilization. These data suggest that the FGF2-stimulated ERK pathway and Runx2 phosphorylation are intact in the Pin1-null mice, indicating that phosphorylation occurs prior to prolyl isomerization and that the MAPK-dependent phosphorylation of the (S/T)P dipeptide is a target of Pin1 (27)(28)(29). Therefore, we examined the ability of MEK1 to increase the level of Runx2 protein, as MEK1 is known to act downstream of FGF2 and to stimulate ERK/MAPK.…”
Section: Pin1-mediated Prolyl Isomerization Is Required For Runx2mentioning
confidence: 99%
“…Pin1, as a MAPK responder, has a crucial role in the oogenesis of a fruit fly (27). In addition, Pin1 target sequences are shared by several protein kinases, such as ERK (27)(28)(29), cyclin-dependent kinase (30,31), and GSK3a (32), indicating that ERK-phosphorylated Runx2 may also be the target of Pin1-mediated conformational and functional alterations.…”
mentioning
confidence: 99%
“…NMP Inhibits RANKL-induced ERK Pathway ActivationGrowth factors that stimulate ERK may ultimately control the activity of c-Fos and AP-1-dependent transcription (25). Recently, it was reported that MIP1␣ (macrophage inflammatory protein 1␣) induces osteoclast formation by activating the MEK/ERK/c-Fos pathway (26) and that vitamin E inhibits RANKL-induced osteoclast differentiation from precursors by suppression of c-Fos expression, possibly through inhibiting ERK (27).…”
Section: Nmp Inhibits Nfatc1 and C-fos Expression And Decreases Ap-1 mentioning
confidence: 99%